Effect of Acupuncture on Postoperative Pain in Patients after Laparoscopic Cholecystectomy: A Randomized Clinical Trial. (13th January 2023) - Wang, Fengxiao; Peng, Pinwei; Zheng, Yixin; Cheng, Shuqun; Chen, Yunfei
Abstract : Objective . To evaluate the efficacy and safety of acupuncture compared to that of parecoxib sodium on postoperative pain (POP), postoperative nausea and vomiting (PONV), and the Bruggemann Comfort Scale (BCS) in patients following laparoscopic cholecystectomy (LC). Methods . Eligible patients admitted to the hospital for LC were randomly allocated to either acupuncture or control groups in a 1 : 1 ratio. The subjects in the acupuncture group received acupuncture while those in the control group were injected by parecoxib sodium at their requests. The pain score, PONV score, and BCS were assessed at 0 h, 6 h, 9 h, and 12 h after operation. The primary outcome was the pain score. The secondary outcomes included the number of patients asking for parecoxib sodium from the two groups at 0–6 h and 6–12 h, PONV score, and BCS score. Results . The pain score of the acupuncture group were lower in acupuncture than that in the control group at 6 h and 9 h after operation (P = 0.002, P = 0.008 ). However, no difference was found at 12 h. Besides, the number of patients administered parecoxib sodium in acupuncture group was less than that in the control group both at 0–6 h and 6–12 h after operation (P = 0.019, P < 0.001 ). Similarly, there were significantly lower levels of PONV score and higher levels of BCS at 6 h after operation in the acupuncture group than in the control group. However, no difference was found at 9 h and 12 h. Conclusion . Acupuncture can clinically improve the short-term treatment of postoperative pain after LC and reduce the request for extra analgesics; therefore, acupuncture might be a potential method as one of multimodal analgesia techniques to treat POP following LC. Trial Registrations . This trial is registered with ChiCTR2000036885 (Chinese Clinical Trial Registry).